Effectiveness of Extension Methods for Knowledge and Skill Development - Dan Singh, R.N. Yadav, D.K. Singh, Gopal Singh, Rajendra Singh and Balvir Singh, (Indian Journal of Extension Education, 2023)
The present study was conducted in Saharanpur and Hapur districts of Western Uttar Pradesh to know theeffectiveness of extension methods. The study reveals that before exposure of different extension methods,about 66.87 per cent vegetable growers had medium knowledge of vegetable cultivation and 34.81percentvegetable growers were unskilled regarding package of practices of vegetable cultivation. The vegetablegrowers gained about 81.50 percent knowledge by the treatment of training + demonstration + literature and76.25 per cent gained skills by the treatment of training + demonstration + literature. The effect of replication(treatment) on knowledge level of the vegetable growers was higher of training + demonstration + literature(35.00%), ranked in first and the same trend was found in skills improvement. It was found that the training+ demonstration + literature was the most effective treatment. The vegetable growers were found in enhancementfrom 5.63 per cent to 23.63 per cent after exposure of different extension methods in the category of high levelof knowledge, this means 319.71 percent knowledge increased in this category. After exposure of differentextension methods, the 100 percent vegetable growers were found skilled regarding vegetable productiontechnology, i.e. nobody was unskilled after exposure of different extension methods.